The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1289/ehp.95103s6135
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of developmental methylmercury exposure.

Abstract: Methylmercury (MeHg) is a global environmental problem and is listed by the International Program of Chemical Safety as one of the six most dangerous chemicals in the world's environment. Human exposure to MeHg primarily occurs through the consumption of contaminated food such as fish, although catastrophic exposures due to industrial pollution have occurred. The fetus is particularly sensitive to MeHg exposure and adverse effects on infant development have been associated with levels of exposure that result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Stern (1993) considered the available human and animal study data addressing developmental endpoints and suggested that the weight of evidence indicated the reference dose ( RfD ) to be 0.07 g /kg /day. With the understanding that the fetus and infant are more sensitive to adverse effects from methylmercury exposure, Gilbert and Grant -Webster (1995 ) used the Iraq episode data (Amin -Zaki et al, 1981;Marsh et al, 1987 ), supported by data on neurobehavioral effects in animals, to develop an RfD range of 0.025 to 0.06 g/kg/ day. Zelikoff et al ( 1995 ) considered various approaches for establishing an RfD based on prenatal methylmercury exposure effects in small mammals, nonhuman primates and humans.…”
Section: Results /Discussionmentioning
confidence: 99%
“…Stern (1993) considered the available human and animal study data addressing developmental endpoints and suggested that the weight of evidence indicated the reference dose ( RfD ) to be 0.07 g /kg /day. With the understanding that the fetus and infant are more sensitive to adverse effects from methylmercury exposure, Gilbert and Grant -Webster (1995 ) used the Iraq episode data (Amin -Zaki et al, 1981;Marsh et al, 1987 ), supported by data on neurobehavioral effects in animals, to develop an RfD range of 0.025 to 0.06 g/kg/ day. Zelikoff et al ( 1995 ) considered various approaches for establishing an RfD based on prenatal methylmercury exposure effects in small mammals, nonhuman primates and humans.…”
Section: Results /Discussionmentioning
confidence: 99%
“…Mercury (Hg) is listed by the International Program of Chemical Safety as one of the most dangerous chemicals in the environment (Gilbert and Grant-Webster, 1995). Humans typically encounter methylmercury (MeHg) from eating fish and seafoods.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in detecting such damage could be due to the nervous system's extraordinary compensatory ability or because the threshold for neural damage has not been crossed. Delayed neurotoxicity, a necessary element of the hypothesis, is clearly established with methylmercury, especially in sensory± motor domains [4,10,32].In reports that may have prompted the original hypothesis, mice exposed during gestation to high levels of methylmercury showed progressive deterioration in swimming ability and other motor endpoints as they aged [34 ± 36]. These early reports have been supplemented by more recent studies with nonhuman primates [32].…”
mentioning
confidence: 99%
“…Difficulties in detecting such damage could be due to the nervous system's extraordinary compensatory ability or because the threshold for neural damage has not been crossed. Delayed neurotoxicity, a necessary element of the hypothesis, is clearly established with methylmercury, especially in sensory± motor domains [4,10,32].…”
mentioning
confidence: 99%